Objects of worship of moslems-shiite of Turkestan - Litvinov, V. P. (Journal of Oriental Studies, 2016)
The article is devoted to an actual problem of religious pilgrimage, through a prism of regional specificity. Proceeding from it, in it the basic centers of religious pilgrimage of moslems-shiite of the Central Asia are considered. Versatile research of the given question is necessary from the point of view of the author for adequate understanding of system which has historically developed in region interreligious attitudes.